Utilization pattern of health care services at a peripheral health care facility of Nepal (Health Renaissance, 2017)
Background: In Nepal, basic health care services at the grass root level are delivered by Subhealth Posts (SHPs) and Health Posts (HPs). The basic aim of these institutions is to deliver essential health care services. In accordance of the Alma Ata declaration on primary health care (PHC) Government of Nepal (GoN) adopted free health care policy on 2006 A.D. to make basic health care services accessible, affordable and available. Thus, SHPs and HPs offer free of cost services to every Nepali citizen. The current study was conducted with the aim of finding utilization pattern of health care services in a peripheral level institution of Sunsari District.Methods: A descriptive study was carried out in Panchkanaya, a sub- health post of Sunsari district utilizing both qualitative and quantitative methods. Data was collected through face to face structured interviews with fifty patients and an in depth interview with in charge of the sub health post. Furthermore, secondary data from records of Health Management Information System (HMIS) of Nepal were also utilized.Results: Out of total patients, most of them were female (67.4%) and majority of patients were from higher age group (>50years).Most of the patients were involved with agriculture as their occupation. Regarding accessibility of health services, most of the respondents could reach sub- health post via walking within 15 minutes. Fifty percent of the patients were satisfied with services provided by the sub-health post. From qualitative aspect, health careservices were under utilized by the people from the northern side of VDC due to inappropriate location of the health post.Conclusion: Health care services were easily accessible although only fifty percent of patients were satisfied by the services.Health Renaissance 2015;13(2): 160-163